2016
DOI: 10.1371/journal.pone.0154134
|View full text |Cite
|
Sign up to set email alerts
|

Guanine-Rich Sequences Are a Dominant Feature of Exosomal microRNAs across the Mammalian Species and Cell Types

Abstract: Exosome is an extracellular vesicle released from multivesicular endosomes and contains micro (mi) RNAs and functional proteins derived from the donor cells. Exosomal miRNAs act as an effector during communication with appropriate recipient cells, this can aid in the utilization of the exosomes in a drug delivery system for various disorders including malignancies. Differences in the miRNA distribution pattern between exosomes and donor cells indicate the active translocation of miRNAs into the exosome cargos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Converting an EXOmotif into a motif present in predominantly cellular microRNAs, or vice versa, altered microRNA localization [78]. A further study confirmed an enrichment of G-rich sequences amongst exosomal microRNAs [81]. Post-transcriptional modifications may also play a role in exosomal targeting of microRNAs.…”
Section: Microrna Loading Into Exosomesmentioning
confidence: 77%
See 1 more Smart Citation
“…Converting an EXOmotif into a motif present in predominantly cellular microRNAs, or vice versa, altered microRNA localization [78]. A further study confirmed an enrichment of G-rich sequences amongst exosomal microRNAs [81]. Post-transcriptional modifications may also play a role in exosomal targeting of microRNAs.…”
Section: Microrna Loading Into Exosomesmentioning
confidence: 77%
“…Specific sequence motifs have been identified that may guide the selective packaging of certain microRNAs [78,81]. Villarroya-Beltri et al identified two EXOmotifs, GGAG and CCCU, which are over-represented in microRNAs localized within exosomes.…”
Section: Microrna Loading Into Exosomesmentioning
confidence: 99%
“…T cells strongly release exosomes with activation . Treg cell exosomes have been studied to some extent, all of which are reports regarding immunosuppressive function.…”
Section: Exosomes From Immune Cellsmentioning
confidence: 99%
“…17,18 T cells strongly release exosomes with activation. 19 Treg cell exosomes have been studied to some extent, all of which are reports regarding immunosuppressive function. CD73 on Treg cells converts extracellular ATP to immunosuppressive ADO and inhibits A2a adenosine receptor-bearing T cells and NK cells.…”
mentioning
confidence: 99%
“…T cells strongly release exosomes with activation [4] . Treg cell exosomes have been studied to some extent, all of which are reports regarding immunosuppressive function.…”
Section: Exosomes From T Cells and Nk Cellsmentioning
confidence: 99%